Pendampingan Pastoral terhadap Majelis Gereja yang Bercerai - Yelniati Mesa Arruan; Arthasasta Arwan; Gista Salu; Mida Palulun; Hesli Restuti (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
This research is library research or research using library methods, the technique used by the author in collecting data is using sources from books, journals and theses which are related to the topic being studied, namely pastoral care. for divorced church boards. The type of research used in this paper is qualitative research which describes the impact of divorce and shows how pastoral care is present in the life of the church council after the divorce. This research aims to minimize the occurrence of divorce, especially in the life of a church council, in maintaining the identity and integrity of a church council.